PENILAIAN KEAMANAN INFORMASI E-GOVERNMENT MENGGUNAKAN INDEX KEAMANAN INFORMASI (KAMI) 4.0 - I Gede Putu Krisna Juliharta; Komang Tri Werthi; Ni Luh Putu Ning Septyarini Putri Astawa (LPPM Universitas Dhyana Pura, 2020)
ABSTRACTIndonesian government uses advanced technology by implementing e-government in improving services to the community and increasing bureaucratic approval. One of the government institutions that request e-government is the Denpasar City government which is managed by the Denpasar City communication and informatics department. In e-government users, it is necessary to implement an information security management system from the electronic system used. The use of KAMI index 4.0 provides a summary of the application of information security systems in the Denpasar city system depending on the level I-I + which has a reactive nature, and needs further development (not feasible) to be able to obtain ISO 27001: 2013 certification.Keywords : e-government; kami; information security; iso 27001.ABSTRAKSIPemerintah Indonesia juga memanfaatkan kemajuan teknologi tersebut dengan menerapkat e-government dalam meningkatkan pelayanan kepada masyarakat dan meningkatkan transparansi birokrasi. Salah satu lembaga pemerintah yang menerapkan e-governement adalah pemerintah kota Denpasar yang dikelola oleh dinas komunikasi dan informatika Kota Denpasar. Dalam pemanfaat e-government perlu dilaksanakan pengukuran terhadap sistem manajemen keamanan informasi dari sistem elektronik yang digunakan. Penggunaan index kami 4.0 memberikan kesimpulan penerapan sistem manajemen keamanan informasi di sistem kota Denpasar berada pada level I-I+ yang memiliki sifat reaktif, dan perlu pengembangan lebih lanjut (tidak layak) untuk bisa mendapatkan sertifikasi ISO 27001:2013Kata kunci : e-government; kami; keamanan informasi; iso 27001.